THE ROLE OF STRETCHING IN THE SPORTS' TRAINING - Vasile Moşuc; Florian Benedek (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
What does the word stretching mean? This is an English word and is translated întindere in Romanian. However, in the sports' field it's got a wider significance, that is a set of stretching exercises having the capacity to improve the body's mobility and flexibility. In sports' training, apart from the warming up itself, stretching has recently appeared. The latter means the revival of joints and tonifying the muscles with the help of stretching movements. These exercises are slow movements that lead to a general improvement of mobility through the stretching of certain groups of muscles. In the sports' training it can be placed as part of the warming up at its beginning or at the end, as a stage of the body's recovery after effort.